FEDERAL RESERVE ACCOUNTABILITY AND REFORM - Kupiec, Paul H. (Assurances et gestion des risques / Insurance and Risk Management, 2015)
The Federal Reserve was created by and enjoys duties and powers delimited by laws passed by Congress. Congress retains the legal right and social responsibility to amend the Federal Reserve Act and related legislation when such amendments are judged to be in the national interest. To exercise this duty, the Congress must have the right to assess the performance of existing Federal Reserve powers and responsibilities. New legislation is required should Congress decide to assess the Federal Reserves’ monetary policy performance using the Government Accountability Office (GAO). The Federal Banking Agency Audit Act of 1978 restricts the GAO from evaluating Federal Reserve activities related to the Fed’s monetary policy functions. No new legislation is required to use the GAO to assess many other Federal Reserve activities and process including the expanded regulatory powers granted to the Federal Reserve and the Board of Governors by the Dodd-Frank Act. Many Federal Reserve regulatory initiatives related to their Dodd-Frank expanded powers merit closer Congressional oversight. In this testimony, I will limit my discussion to three areas that have especially important ramifications for the safety and vitality of the entire U.S. financial system: The Congress should exercise closer oversight over the Federal Reserve’s ongoing interactions with international standard-setting bodies like the Financial Stability Board, the International Association of Insurance Supervisors, and the Basel Committee on Banking Supervision. Congresses should instruct the GAO to assess the costs, benefits, and processes associated with the recurring Board of Governors stress tests mandated by Section 165 of the Dodd-Frank Act. These stress tests are very resource-intensive, both for banks and for the banking regulators, and there is little evidence that they are a cost effective and objective means for regulating individual financial institutions. Congress should assess potential conflicts that may be developing between the Federal Reserve’s Dodd-Frank expanded powers over the domestic insurance industry and state insurance regulations. There are indications that new Federal Reserve examination and capital policies for insurers affiliated with a depository institution may be generating serious conflicts with existing state insurance supervision and regulation, contrary to the intent of the Dodd-Frank Act.